2023
DOI: 10.1021/jacs.3c07048
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Strain-Mediated Ultrathin Ceria Nanoantioxidant

Cong Liu,
Lin Gui,
Jia-Jia Zheng
et al.

Abstract: Metal oxide nanozymes have emerged as the most efficient and promising candidates to mimic antioxidant enzymes for treatment of oxidative stress-mediated pathophysiological disorders, but the current effectiveness is unsatisfactory due to insufficient catalytic performance. Here, we report for the first time an intrinsic strain-mediated ultrathin ceria nanoantioxidant. Surface strain in ceria with variable thicknesses and coordinatively unsaturated Ce sites was investigated by theoretical calculation analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…(B) SOD-like activity and Cu 2 O@His concentration relationships. (C) IC 50 comparison diagram of SOD-like activity nanozymes. , Size: MOF-818 (240 nm), CeVO 4 (15 nm), Mn 3 O 4 flowers (180 nm), Cu-Sazyme (∼300 nm), NiO nanoflowers (∼2.6 μm), Ceria nanocubes (6.44 nm ±0.42), Ultrathin ceria (50.09 ± 2.96 nm). (D) EPR spectra for O 2 •– scavenging ability of Cu 2 O@His.…”
Section: Resultsmentioning
confidence: 99%
“…(B) SOD-like activity and Cu 2 O@His concentration relationships. (C) IC 50 comparison diagram of SOD-like activity nanozymes. , Size: MOF-818 (240 nm), CeVO 4 (15 nm), Mn 3 O 4 flowers (180 nm), Cu-Sazyme (∼300 nm), NiO nanoflowers (∼2.6 μm), Ceria nanocubes (6.44 nm ±0.42), Ultrathin ceria (50.09 ± 2.96 nm). (D) EPR spectra for O 2 •– scavenging ability of Cu 2 O@His.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous theoretical and experimental reports have highlighted the effects of strain on catalysts. 58–61 For instance, Fan et al reported enhanced catalytic performance in the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) of Pt-doped Ti 2 CX 2 (X = O and C) through strain engineering, attributed to d-band centers and work functions. 62,63 Compared to the α-phase and β-phase of GeSe, γ-GeSe exhibits in-plane isotropic elastic modulus characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the enrichment of local concentration of reactants through wettability and/or micro/nanostructure modulation of electrocatalysts were found beneficial for boosting reaction kinetics. [21][22][23] While, the reactant enrich-ment effect for heterogeneous transition metal-coordinated electrocatalysts in 2e-ORR yet remains unclear.…”
Section: Introductionmentioning
confidence: 99%